Facial Asymmetry Index: Validation and Applications in Various Smile Restoration Techniques - Malm, Ian-James; Albathi, Monirah; Byrne, Patrick; Ishii, Masaru; Ishii, Lisa; Boahene, Kofi (Facial Plastic Surgery, 2018)
Consistent and objective evaluation of the paralyzed face is imperative for documenting preoperative findings and assessing postoperative outcomes of reanimation techniques. Static and dynamic facial asymmetry are the key features of the paralyzed face. To date, there is no consensus among surgeons on how best to document facial asymmetry. The authors propose a Facial Asymmetry Index (FAI) as an objective measure of facial asymmetry and validate its use and reliability across numerous reanimation techniques. Frontal photographs of patients with unilateral facial nerve paralysis were analyzed. The length from the medial canthus to the ipsilateral oral commissure was compared between affected and nonaffected sides. The FAI is the difference between the two values, with a higher value reflecting poorer facial symmetry. Validation and reliability testing was then performed. There was a consistent decrease in the FAI with procedural intervention (FAI pre = 10.1, FAI post = 3.17; p < 0.0001). Furthermore, there was excellent inter- and intrarater reliability among independent judges. The FAI is a powerful and accessible tool to quantify operative outcomes for many lower facial nerve reanimation techniques.
Keywords: facial paralysis; facial reanimation; outcome assessment